2020
DOI: 10.1101/2020.03.30.016857
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Abundance and localization of human UBE3A protein isoforms

Abstract: Loss of UBE3A expression, a gene regulated by genomic imprinting, causes Angelman Syndrome (AS), a rare neurodevelopmental disorder. The UBE3A gene encodes an E3 ubiquitin ligase with three known protein isoforms in humans. Studies in mouse suggest that the human isoforms may have differences in localization and neuronal function. A recent case study reported mild AS phenotypes in individuals lacking one specific isoform. Here we have used CRISPR/Cas9 to generate isogenic human embryonic stem cells (hESCs) tha… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 23 publications
1
16
0
Order By: Relevance
“…Considering the very good match of the transcriptome data (this study) and proteome data ( 9 , 26 ), the expression of distinct human UBE3A isoforms appears to be entirely governed by alternative splicing. But unlike human UBE3A isoforms, our data suggest that mouse UBE3A protein isoforms arise to a large extent by alternative translation.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Considering the very good match of the transcriptome data (this study) and proteome data ( 9 , 26 ), the expression of distinct human UBE3A isoforms appears to be entirely governed by alternative splicing. But unlike human UBE3A isoforms, our data suggest that mouse UBE3A protein isoforms arise to a large extent by alternative translation.…”
Section: Discussionmentioning
confidence: 55%
“…In an elegant study published alongside our own, Chamberlain and co-workers successively deleted each of the three UBE3A isoforms from human iPS-derived neurons, in turn enabling the focused study of the remaining UBE3A proteins ( 26 ). Despite our different experimental approaches (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…AS hiPSCs were developed in the Chamberlain and Lalande groups and obtained from Kerafast ( Chamberlain et al., 2010 ). UBE3A double-knockout H9 cells (H9 UBE3A m-/p- ) with a 66 kb deletion (chr15: 25,338,949–25,405,676) were provided by Dr. Stormy Chamberlain (UCONN) ( Sirois et al, 2020 ). Cells were maintained in tissue culture dishes (Fisher Scientific Corning Costar) coated with 0.5 mg/cm 2 vitronectin (VTN-N; Thermo Fisher Scientific) in E8 medium (Thermo Fisher Scientific) and passaged using standard protocols.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to its imprinted expression, one of the salient molecular features of UBE3A is its nuclear localization in neurons, which also occurs perinatally and in the first couple postnatal weeks of murine neurodevelopment ( Burette et al., 2017 ; Judson et al., 2014 ). This localization may be regulated by shifts in the expression levels of UBE3A isoforms ( Sirois et al, 2020 ). It was recently shown that mice lacking a nuclear UBE3A isoform exhibited electrophysiological and behavioral deficits similar to those in other AS model mice ( Avagliano Trezza et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to AS neurons, UBE3A-overexpressing neurons do not exhibit polarization problems [ 69 ]. Another report provides evidence that isoform 1 accounts for the majority of UBE3A in neurons [ 70 ]. Moreover, knockdown of alternatively spliced Ube3a1 devoid of its catalytic activity prompts robust dendritic growth, reduces the volume of spines and leads to decreased synaptic transmission.…”
Section: Isoform-specific Neuromorphoregulatory Roles Of Ube3amentioning
confidence: 99%